A COMPARATIVE STUDY OF TIME-RELATED PHRASEOLOGICAL UNITS IN ENGLISH AND UZBEK FROM A CULTURAL LINGUISTICS PERSPECTIVE - Shakhnoza Rustamova (International Journal of Literature and Language Studies, 2026)
Abstract. This article presents a comparative linguocultural analysis of phraseological units related to the concept of time in the English and Uzbek languages. Time is an integral part of human life and is undoubtedly reflected in every language and culture. Time-related phraseological units in English and Uzbek reveal how people perceive the concept of time and reflect the traditions and values associated with it. The study highlights the close relationship between the concept of time, folk cognition, national mentality, and cultural values. The representation of the concept of time in phraseological units of English and Uzbek is examined from a conceptual perspective. Furthermore, the article discusses cultural linguistics as one of the major directions of modern linguistics and analyzes the similarities and differences between English and Uzbek time-related phraseological units through a comparative linguocultural approach.